Antibacterial Activities of Green Basil (Ocimum Violaceum) Essential Oil and Derivatives By MAOS (Microwave Assisted Organic Synthesis) Against Staphyllococus Aureus and Escherichia Coli - Dwiarso Rubiyanto; Hady Anshory; Hardjono Sastrohamidjojo; Chairil Anwar (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2014)
Green basil (Ocimum violaceum , Linn.) plantis part of the varieties of basil (Ocimum basilicum, Linn.). Green basil essential oil (GBEO) contain chemical compounds that have an anti- bacterial activities . Methyl eugenol and methyl chavikol are in green basil oil has the potential to be used as a material which is biologically active. Conversion reaction of the compounds in GBEO with MAOS methods (microwave assisted organic synthesis) aims to obtain properties of the main chemical component in a wider sweet basil oil, and are also useful in an attempt to gain more valuable compounds for commercial and higher. The results showed that the optimum reaction conditions on the conversion reaction of compounds in GBEO with MAOS method with ethylene glycol as a solvent is 10 % KF/Al2O3as catalyst and reaction time 3 minutes , while the solvent is glycerol 10 % KF/Al2O3as catalyst and reaction time 2 minutes . Comparison of anti-bacterial activity resulting from this research are : the inhibitory activity to the growth of S. aureus bacteria have the following order : GBEO > green basilEG10-3 > green basil G10-2> amoxicillin with each inhibition zone diameter amounted to 30.7 mm, 21.1 mm, 18.2 mm and 13.4 mm. While the inhibitory activity to the growth of E.coli bacteria are : GBEO> green basil G10-2 >green basil EG10-3 > amoxicillin with each inhibition zone diameter of 21.1 mm, 15.6 mm , 15.2 mm and 7.9 mm . GBEO and its derivatives have minimal inhibitory concentrations below 1.25 %. From the results of the study found that the main derivates obtained are p-methoxy anisaldehyde , caryophyllene oxide , 3-methoxy cinnamaldehyde , humulena oxide and delta cadinol